2018
DOI: 10.1002/jctb.5707
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the nitrification and sulfide‐driven autotrophic denitrification processes in a single reactor using oxidation–reduction potential as an indicator of the process effectiveness

Abstract: BACKGROUND: This paper evaluates the nitrification and sulfide-driven autotrophic denitrification processes in a structured-bed reactor subjected to recirculation and intermittent aeration (SBRRIA) applied to the post-treatment of an anaerobic effluent. The SBRRIA reactor was operated during 130 days in which influent sulfide concentrations varied between 220.1 and 231.0 mg TDS L −1 (TDS, total dissolved solids). Temporal tests were performed to elucidate the dynamics and sulfide impacts on combined processes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The presence of biofilm also can help to maintain the AOB and NOB activity in the system with the presence of inhibitors. For instance, dos Santos et al using a biofilm system (structured‐bed reactors subjected to recirculation and intermittent aeration), could keep the nitrifying activity in the presence of total dissolved sulfide (TDS) at concentrations as high as 230 mg S 2− L −1 , and COD concentrations ≈50 mg L −1 . According to Parkin and Speece, attached growth systems are more resistant to sulfide toxicity than suspended ones because of the higher SRT at relatively low HRT and the production of extracellular polymeric substances (EPS), which act as a diffusion barrier between cells and improper environments …”
Section: Resultsmentioning
confidence: 99%
“…The presence of biofilm also can help to maintain the AOB and NOB activity in the system with the presence of inhibitors. For instance, dos Santos et al using a biofilm system (structured‐bed reactors subjected to recirculation and intermittent aeration), could keep the nitrifying activity in the presence of total dissolved sulfide (TDS) at concentrations as high as 230 mg S 2− L −1 , and COD concentrations ≈50 mg L −1 . According to Parkin and Speece, attached growth systems are more resistant to sulfide toxicity than suspended ones because of the higher SRT at relatively low HRT and the production of extracellular polymeric substances (EPS), which act as a diffusion barrier between cells and improper environments …”
Section: Resultsmentioning
confidence: 99%
“…Bench-scale investigations have shown the potential of applying the structured bed reactors subjected to recirculation and intermittent aeration (SBRRIA) to remove organic matter and nitrogen compounds from different wastewaters (Almeida et al, 2018;Barana et al, 2013;Correa et al, 2018;Moura et al, 2012Moura et al, , 2018Santos et al, 2016Santos et al, , 2018Silva et al, 2018;Wosiack et al, 2015). In the structured bed reactor, the biofilm grows adhered to a polyurethane (PU) foam that serves as a support material.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] On the other hand, the kinetics of nitrification in the simultaneous presence of sulfide and organic has not been proposed up to date. There are studies which reported the single effect of sulfide on nitrification [7][8][9] and also several studies about nitrification in the presence of organic matter. [10,11] However, the evaluation of a kinetic model involving the simultaneous effects of sulfide and organic matter has not been proposed and has never been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%